'... conceived by the Holy Spirit and born of the Virgin Mary': The exposition of the Heidelberg Catechism in the light of present-day criticism - van Wyk, Ignatius W. C. (HTS Teologiese Studies / Theological Studies, 2014)
The article is a contribution to the 450 year celebrations of the Heidelberg Catechism (HC). Sunday 14, Questions and Answers 35 and 36 receive attention. It deals with the two statements of the creed '... conceived by the Holy Spirit and born of the Virgin Mary'. The exposition of the HC is compared to the catechisms of Zacharias Ursinus and John Calvin in order to capture something about the historicity of the text. The exposition of the creed is an on-going process. Karl Barth, Eberhard Busch and Jan Milič Lochman are good examples of Reformed theologians who remain faithful to the intention of the HC, but who explain these statements with present-day criticism in mind. The exposition of Peter Berger is valuable because this sceptic argues that the opinion of modern, liberal Protestantism is of no value. The article concludes that the 'virgin birth' as such has no great value. It is only one aspect of the Christian gospel. It also does not proof the divinity of Christ. The divinity of Christ is presupposed.
Free
Keywords: CALVIN; Jean; 1509-1564; HEIDELBERGER Katechismus; HOLY Spirit; MARY; Blessed Virgin; Saint; PROTESTANT history; URSINUS; Zacharias